Characterization of the molecular interactions between Kaiso and CTCF using AlphaFold2 and molecular dynamics simulations - Thapa, Bidhya; Adhikari, Narayan Prasad (BIBECHANA, 2024)
CCCTC-binding factor (CTCF) is an architectural protein that plays a crucial role in global chromatin organization and remodeling via its interaction with several protein partners. The interaction between Kaiso and CTCF regulates the enhancer-blocking function of CTCF. Despite the important biological function of their interactions, structural characterization of the Kaiso-CTCF complex has yet to be carried out. In this work, we have employed modeling and molecular dynamics (MD) simulation to predict the complex between Kaiso and CTCF and investigate its structural features. We have employed the neural network-based modeling method Alphafold2 to predict the complex between Kaiso and CTCF, and the MD simulation was used to explore the detailed dynamics of the interactions involved in complex formation and stabilization. We predicted the key residues and their role in the binding of Kaiso to CTCF. Our results show that the hydrophobic interactions between the inter-facial residues play a significant role in forming the Kaiso-CTCF complex. In addition, several non-covalent interactions, such as hydrogen bonds and electrostatic and van der Waals interactions, stabilize the complex. The significant value of hydrophobic contact area and binding free energy signifies the stability of the predicted Kaiso-CTCF complex.